Perspektif Hukum Ekonomi Syariah: Kebijakan Pemerintah Dalam Mengatasi Perekonomian Masa Pandemic Covid 19 - Kusrini, Eni (Sharia Faculty Islamic Economic Law Study Department, 2021)
Pandemic covid 19 is increasingly significant in Indonesia, so the economy is unstable. This is caused by paralysis of activities in all dimensions of life so that the economy is completely paralyzed. Government policy is needed to be able to survive in the covid pandemic 19, so as to suppress the rate of inflation and the community is able to survive in the midst of the economic crush in accordance with Islamic economic law studies. Islamic scientific studies in the realm of sharia macroeconomics need to be carried out in order to be able to suppress and even overcome the problems that occur in the State of Indonesia today. How the government efforts are able to work together with all the various communities able that this outbreak is able to be overcome and not prolonged.